2020
DOI: 10.3390/su12239853
|View full text |Cite
|
Sign up to set email alerts
|

Measuring and Monitoring Sustainability in Listed European Football Clubs: A Value-Added Reporting Perspective

Abstract: All sports have their roots and connection in some way to the Olympic spirit, and therefore fall within the vision and mission of the Olympic Committee, which has a central aim of “building a better world”. This is a fundamental value of the Olympics and sustainability is a “working principle” of this. This research analyses the performance of professional European football teams that are publicly listed on stock markets, analysing their income statements and factoring in how the value-added perspective is imp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 52 publications
0
14
0
Order By: Relevance
“…The values promoted by sport seem to be as important now as the sports results and financial results achieved by sports clubs. Some researchers point to the significant potential of creating added value by football clubs not only through the Pobrane z czasopisma Annales H -Oeconomia http://oeconomia.annales.umcs.pl Data: 26/09/2022 08:27:34 U M C S generated financial results, the sports level represented by the team and individual players, but also through orientation towards sustainable development (Faccia et al, 2020). Moreover, sustainable development as an element of fan welfare maximization is indicated as one of the most important factors affecting the image and financial results of a football club (Cruz et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The values promoted by sport seem to be as important now as the sports results and financial results achieved by sports clubs. Some researchers point to the significant potential of creating added value by football clubs not only through the Pobrane z czasopisma Annales H -Oeconomia http://oeconomia.annales.umcs.pl Data: 26/09/2022 08:27:34 U M C S generated financial results, the sports level represented by the team and individual players, but also through orientation towards sustainable development (Faccia et al, 2020). Moreover, sustainable development as an element of fan welfare maximization is indicated as one of the most important factors affecting the image and financial results of a football club (Cruz et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…In the scientific literature, the issue of the relationship between social responsibility and sport, despite the dynamic increase in popularity in recent years, has been discussed relatively rarely (Mallen, Adams, Stevens, & Thompson, 2010;Mallen, Stevens, Adams, & McRoberts, 2010;Tranter & Lowes, 2009;Faccia et al, 2020). As Dingle (2016) notes, recent years have seen a kind of clear increase in the number of journals and research undertaken in this area, but their characteristics still seem to reflect the level of early years of research on social responsibility in non-sport areas.…”
Section: Introductionmentioning
confidence: 99%
“…The review of the related literature showed that a number of studies have focused on sustainability analysis in football clubs (Faccia et al ., 2020; Fernández-Villarino, 2021), economic sustainability of inter-college track and field (Mitten and Ross, 2013), financial sustainability of charitable organizations and sports associations (Bingham and Walters, 2013), social sustainability of the commercialization of football (Brandt and Kurscheidt, 2022), financial sustainability and gender diversity in professional football (Clarkson and Philippou, 2022), examination of the strategic involvement of stakeholders in the efficiency of non-profit sports organizations from a sustainability perspective (Miragaia et al ., 2017); promotion of sustainable mobility with the help of Swiss sports clubs (Moser et al ., 2019); sustainability in participatory sports events (Hugaerts et al ., 2021); financial sustainability management and profit management in Spanish sports federations (Guevara et al ., 2021); sports indicators of the prediction of the sustainability of sports development (Oluwatoyin et al ., 2021), sustainability and social responsibility of Romanian sports organizations (Barbu et al ., 2022), impacts of UEFA Europa League and UEFA Champions League on financial sustainability (Dantas et al ., 2020); sports for sustainability and sustainable development (Millington et al ., 2022), and business model classifications which result in the development of sustainable football-based economy for European professional football clubs (Buck and Ifland, 2022). Moreover, research has focused on accounting, finance and conflict in football arenas (Adams et al ., 2023), the strategic and financial decision-making of top football clubs in Europe (Toma and Campobasso, 2023), civil society organizations as factors of social change: the participation of football clubs with sustainability (Lozano and Barreiro-Gen, 2023), and governments as hinderances to the development of professional football: the case of Iran (Biglari et al ., 2023).…”
Section: Literature Reviewmentioning
confidence: 99%
“…In Sustainability Reports, Value-Added is considered as the difference between the revenues and costs of production. It can be therefore considered as the "difference between revenues and costs incurred for the purchase of production factors from other companies, and thus represents the value that the internal production factors of the company, risk capital and labour, have "added" to the inputs attained from outside" [47].…”
Section: Value-added Income Statementmentioning
confidence: 99%